2007
DOI: 10.1097/01.mlg.0000249954.77551.98
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous Malformations of the Tongue: A Spectrum of Disease

Abstract: This study suggests that tongue AVM can occur within a spectrum of disease with different clinical presentations, radiographic findings, and histology among patients with focal versus advanced lesions. Inadequate treatment is thought to contribute to collateral flow and disease progression in advanced AVM, making further management difficult. However, focal tongue AVM may represent early lesions that are more amenable to surgical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 15 publications
(40 reference statements)
3
50
0
Order By: Relevance
“…The cure rate of Schobinger stage II AVMs with the current standard treatment, total resection after embolization, has been reported as 62% [1] . Richter et al [3] reported the surgical management and results for 11 cases of AVMs of the tongue. They emphasized the broad spectrum of this disease and divided their cases into 2 different types, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cure rate of Schobinger stage II AVMs with the current standard treatment, total resection after embolization, has been reported as 62% [1] . Richter et al [3] reported the surgical management and results for 11 cases of AVMs of the tongue. They emphasized the broad spectrum of this disease and divided their cases into 2 different types, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…They usually exist bilaterally and are fed by multiple arteries, including lingual, facial and internal maxillary arteries. Progressive growth usually manifests after intervention including embolization, ligation and insufficient surgical resection [3,18] . The standard treatment for this category is embolization followed by combined wide total excision with flap reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…It is inexpensive, quick, and convenient and there are no known harmful effects, since it uses non-ionising radiation suited to the soft tissues and it does not cause any pain. Ultrasound can be used to guide the optical fibres to the appropriate disease volume, enabling more accurate evaluation of treatment doses [17,21].…”
Section: Photodynamic Therapy (Pdt)mentioning
confidence: 99%
“…7 Arteriovenous malformations have different histopathologic features. 9 The pathogenesis of AVMs has still not been explained exactly. It is unknown whether these lesions are congenital or not.…”
Section: Approach Of Dental Treatment In Arteriovenous Vascular Malfomentioning
confidence: 99%